Forecasting GIC Activity Associated With Solar Wind Shocks for the Australian Region Power Network - R. A. Marshall; E. A. Pearce; C. L. Waters; M. Terkildsen (Space Weather)
Abstracts Space weather induced Geomagnetically Induced Currents (GICs) that are hazardous to power networks at high latitudes are often the result of rapid changes in near‐Earth space current systems such as the auroral electrojets and field‐aligned currents. GIC activity at low‐middle latitudes may be driven by currents that are more relevant to these regions such as the ring or magnetopause current systems. Solar wind shocks create rapid changes in the magnetopause current that manifest as large step changes in the geomagnetic field at the Earth's surface, often referred to as geomagnetic sudden impulses (SIs), that are effective drivers of GIC activity in power networks at low‐middle latitudes. This paper describes the results of a study into the relationship between the driver of SIs, solar wind shocks, and their potential impact on power systems in the Australian region, as quantified by a GIC‐index. The initial data set for analysis was produced by programmatically scanning solar wind data obtained from the ACE satellite spanning the period 1998–2008 for solar wind shocks. For each identified solar wind shock, geomagnetic field data from the Australian region were analyzed to determine the corresponding SI and GIC‐index. Statistical analyses of GIC‐indices and various solar wind parameters associated with the shocks resulted in an empirical model that is a function of solar wind dynamic pressure, geomagnetic latitude, and change in solar wind speed with good operational predictive capability. This model was further assessed using online catalogs of solar wind shock events.